Socioeconomical Factors Associated With Pediculosis (Phthiraptera: Pediculidae) in Athens, Greece. Issue 4 (1st May 2016) - Tagka, Anna; Lambrou, George I.; Braoudaki, Maria; Panagiotopoulos, Takis; Papanikolaou, Eleni; Laggas, Dimitris
Abstract: Pediculosis in humans and especially in children is a very common dermatological disorder caused by the ectoparasite Pediculus humanus capitis De Geer. We investigated the socioeconomic factors affecting the prevalence of pediculosis in the Greek urban area of Athens during 2004–2006. The target population consisted of children from kindergartens. In total, 434 children from single- or two-parent families were investigated with respect to socioeconomic factors such as education, income and family composition, and the prevalence of pediculosis. The overall pediculosis rate was 5.30%. Head louse infestations were significantly higher in female children and in two-parent families. Lice infestations peaked in low- and medium-income families. Head louse infestation rates were influenced by income, parents' education, and nationality.